Characterization of the Myostracum Layers in Molluscs Reveals a Conservative Shell Structure - Dong, Wentao; Huang, Jingliang; Liu, Chuang; Wang, Hongzhong; Zhang, Guiyou; Xie, Liping; Zhang, Rongqing (Frontiers in Marine Science, 2022)
Molluscs produce rigid shells to protect their soft bodies from predators and physiochemical violations. The soft tissues attach to shells via the myostracum layer (also called adductor muscle scar, AMS) which bears tremendous contract force and is of vital importance to the survival of the molluscs. Considering the prevalence of tissue-shell attachment in molluscs, we speculate that certain homology may be shared among varied species. To test this speculation, scanning electron microscopy and Raman spectrum were applied to analyze the microstructure and calcium carbonate polymorphs of the myostracum in most of the molluscan classes. It was found that all the tested molluscan classes and genera contain similar columnar prisms which were vertically aligned and were composed of aragonite. Moreover, this structure was found in fossils dating back to more than 250 million years ago. Such peculiar mineral structure may contribute to the loading contract force, thus being evolutionally conservative among varied species and for hundreds of million years. Our study underscores the vital impact of physiological functions on the evolution of the shell structure.